Marriage contract: controversial issues of definition and procedure for conclusion - Zhunussova, T.B. (Bulletin of the Karaganda University “Law Series”, 2022)
The marriage contract has not yet received a sufficiently wide distribution in the Republic of Kazakhstan. At the same time, with the help of a marriage contract, it is possible to settle a significant range of relations in matters of property relations between spouses, as well as to protect the property rights of children born or adopted in marriage. The legal regulation of marriage agreements (contracts) has so far been rather schematic, and the law enforcement practice for their accounting has not yet been properly developed. However, certain issues become problematic already when assessing the existing legislative requirements in the current civil and family legislation of Kazakhstan, which requires the introduction of separate additions and adjustments. The history of the legal regulation of the marriage contract does not have a long duration, although certain issues of regulation of property relations took place even in the customary law of the Kazakhs. The study is carried out mainly using a special legal methodology in compliance with general scientific research methods, in particular, the dialectical method. Based on the evaluation of the results of theoretical studies and the current legislation, conclusions are formulated regarding the clarification of the legal nature of the marriage contract, and proposals are developed to clarify certain provisions relating to the issues of concluding a marriage contract in individual cases.